Standing on the Shoulders of Giants: Entrepreneurship and Path Dependency in a Regional Context - Sabrina Florkowski (European Regional Science Association (ERSA), 2010)
A student of regional development can identify two general types of explanations for why some regions develop as they do. The first explanation relates to the emergence of innovative activities carried out by pioneering entrepreneurs that may transform the society and economy. In literature, this is referred to as impressive stories of renewal and change, where regions have changed from old and heavily industrialized regions to modern high tech poles, examples being Teesside in Northeast of England and the √\~nresund Region in Denmark and Sweden. The other type of explanation is related to path dependency, where present developments build on past decisions and activities. In apparent contrast to the first explanation, path dependency is often seen as negative constraints for future development where some regions continue to develop along established regional trajectories and ultimately result in lock-ins. In this perspective, regions may be caught in destructive path dependency processes and only by breaking free from their constraining past they can change their declining path. This type of regional development process is thus practically "entrepreneurless". This paper challenges the general way of dichotomizing between entrepreneurship and path dependency as two opposing concepts. Rather, we posit that these concepts are related to each other and we argue that such a view can provide a better understanding of regional development processes. An important building block for our theoretical discussion is the idea that even such disruptive activities as revolutions are never really discontinuous as informal constraints are imbedded in societies. Thus, entrepreneurs can create new regional paths, but they are also to some extent related to existing patterns and behavior in the region. Against this background, the aim of the paper is to build a conceptual framework with several propositions that discusses the relationship between path dependency and entrepreneurship in a regional context, focusing in particular on their complementary nature. The conceptual framework proposed in this paper suggests that entrepreneurs can "stand on the shoulders of giants" by using prior knowledge embedded in the regional infrastructure to identify new opportunities which then can be outside of the established regional trajectories.
Keywords: 330; Path Dependency; Entrepreneurship; Regional Development; Innovation